A multidimensional magnetic resonance histology atlas of the Wistar rat brain - Johnson, G.; Calabrese, E.; Badea, A.; Paxinos, G.; Watson, Charles (Academic Press, 2012)
We have produced a multidimensional atlas of the adult Wistar rat brain based on magnetic resonance histology (MRH). This MR atlas has been carefully aligned with the widely used Paxinos–Watson atlas based on optical sections to allow comparisons between histochemical and immuno-marker data, and the use of the Paxinos–Watson abbreviation set. Our MR atlas attempts to make a seamless connection with the advantageous features of the Paxinos–Watson atlas, and to extend the utility of the data through the unique capabilities of MR histology: a) ability to view the brain in the skull with limited distortion from shrinkage or sectioning; b) isotropic spatial resolution, which permits sectioning along any arbitrary axis without loss of detail; c) three-dimensional (3D) images preserving spatial relationships; and d) widely varied contrast dependent on the unique properties of water protons. 3D diffusion tensor images (DTI) at what we believe to be the highest resolution ever attained in the rat provide unique insight into white matter structures and connectivity. The 3D isotropic data allow registration of multiple data sets into a common reference space to provide average atlases not possible with conventional histology. The resulting multidimensional atlas that combines Paxinos–Watson with multidimensional MRH images from multiple specimens provides a new, comprehensive view of the neuroanatomy of the rat and offers a collaborative platform for future rat brain studies.